Protective effects of rice bran hydrolysates on heart rate variability, cardiac oxidative stress, and cardiac remodeling in high fat and high fructose diet-fed rats - Ketmanee Senaphan; Upa Kukongviriyapan; Pisit Suwannachot; Geerasak Thiratanaboon; Weerapon Sangartit; Supawan Thawornchinsombut; Akkasit Jongjareonrak (Asian Pacific Journal of Tropical Biomedicine, 2021)
Objective: To examine the ameliorative effect of rice bran hydrolysates (RBH) on metabolic disorders, cardiac oxidative stress, heart rate variability (HRV), and cardiac structural changes in high fat and high fructose (HFHF)-fed rats. Methods: Male Sprague-Dawley rats were daily fed either standard chow diet with tap water or an HFHF diet with 10% fructose in drinking water over 16 weeks. RBH (500 and 1 000 mg/kg/day) was orally administered to the HFHF-diet-fed rats during the last 6 weeks of the study period. At the end of the treatment, metabolic parameters, oxidative stress, HRV, and cardiac structural changes were examined. Results: RBH administration significantly ameliorated metabolic disorders by improving lipid profiles, insulin sensitivity, and hemodynamic parameters. Moreover, RBH restored HRV, as evidenced by decreasing the ratio of low-frequency to high-frequency power of HRV, a marker of autonomic imbalance. Cardiac oxidative stress was also mitigated after RBH supplementation by decreasing cardiac malondialdehyde and protein carbonyl, upregulating eNOS expression, and increasing catalase activity in the heart. Furthermore, RBH mitigated cardiac structural changes by reducing cardiac hypertrophy and myocardial fibrosis in HFHF-diet-fed rats. Conclusions: The present findings suggest that consumption of RBH may exert cardioprotective effects against autonomic imbalances, cardiac oxidative stress, and structural changes in metabolic syndrome.